Study on Analog Front End of Passive UHF RFID Transponder - Hadi, D. A.; Soin, N. (2009)
In this paper, an overview of passive Ultra High Frequency (UHF) Radio Frequency Identification (RFID) is presented. This literature review emphasis on the analog front end part of the RFID transponder based on several published papers conducted by previous researchers. A passive UHF RFID transponder chip design was proposed using 0.18 μm standard CMOS process. It is estimated to have power of 1μW and high efficiency that greater than 32%. This design will work in the range of frequency between 900MHz to 960MHz.